2020
DOI: 10.1111/rec.13215
|View full text |Cite
|
Sign up to set email alerts
|

Coastal wetland restoration improves habitat for juvenile sportfish in Tampa Bay, Florida, U.S.A.

Abstract: Increasing human populations and urban development have led to losses of estuarine habitats for fish and wildlife. Where resource managers are restoring coastal wetlands, in addition to meeting goals related to hydrologic connectivity, biodiversity, and recreational opportunities, efforts are being made to provide habitat that is suitable for juvenile sportfish. An 18-month study was conducted to compare juvenile sportfish use of natural, restored, and impacted sites along Tampa Bay, Florida, shorelines. Juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Recently, fish abundance, richness and diversity were found to be similar between natural and restored marsh shorelines along the Florida west coast, and higher relative to impacted shorelines [57]. Specifically, sportfish densities at those sites were comparable between natural and restored shorelines and higher than impacted shorelines, which included five of the same species highlighted in the current study (C. nebulosus, C. undecimalis, L. griseus, P. cromis, Sciaenops ocellatus) [14]. Higher abundances and species richness of fishes have also been observed three years post construction of sill living shorelines (i.e., a hybrid technique which incorporates offshore rock material with shoreline marsh plantings), compared to unvegetated shoreline and natural controls, including some juvenile species observed in our study (C. nebulosus, L. griseus, S. ocellatus) [22].…”
Section: Living Shorelinessupporting
confidence: 56%
See 4 more Smart Citations
“…Recently, fish abundance, richness and diversity were found to be similar between natural and restored marsh shorelines along the Florida west coast, and higher relative to impacted shorelines [57]. Specifically, sportfish densities at those sites were comparable between natural and restored shorelines and higher than impacted shorelines, which included five of the same species highlighted in the current study (C. nebulosus, C. undecimalis, L. griseus, P. cromis, Sciaenops ocellatus) [14]. Higher abundances and species richness of fishes have also been observed three years post construction of sill living shorelines (i.e., a hybrid technique which incorporates offshore rock material with shoreline marsh plantings), compared to unvegetated shoreline and natural controls, including some juvenile species observed in our study (C. nebulosus, L. griseus, S. ocellatus) [22].…”
Section: Living Shorelinessupporting
confidence: 56%
“…Many studies have examined the response of resident fishes and invertebrates to restoration, while relatively few have targeted more transient and higher trophic species. Sportfish observations in former studies were generally in low abundances, e.g., [25,26,28], while a recent targeted sportfish study allowed for direct comparisons, which found them to have comparable densities between natural and restored coastal wetlands [14]. Furthermore, restoration benefits impact species to varying degrees and may take time to accrue, as the majority of increased gross fish production does not occur for up to two years at oyster reefs [17] and three years at living shorelines [22], similar to the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations